Upaya Penanganan TB Paru pada Anak Perempuan Usia 1 Tahun di Puskesmas Babah Buloh Tahun 2025 - Farah Agustari; Hendra Wahyuni (Pusat Riset dan Inovasi Nasional, 2026)
Tuberculosis (TB) is a chronic, infectious disease caused by the bacterium Mycobacterium tuberculosis. Primary infection occurs upon first exposure to bacillary tuberculosis, which often occurs in childhood, hence the term